PENERAPAN MODEL EVALUASI STAKE (COUNTENANCE) UNTUK MENGEVALUASI PEMBELAJARAN DASAR - DASAR AKUNTANSI - Siswanto Siswanto (Universitas Negeri Yogyakarta, 2009)
This study was aimed at evaluating the Instructional process of Introduction toAccounting subject in Accounting Education Department, Social Science and EconomicFaculty, State University of Yogyakarta, including (1) the students’ educationalbackground that supports the teaching; (2) the students’ learning motivation; (3) theavailability and completeness of supporting facilities and infrastructure; (4) the use offacilities and infrastructure to support the teaching process (5) the teaching process;(6) students’ understanding after the teaching process, and (7) the students’ learningachievement.This study was an evaluation study using qualitative descriptive data with theStake model evaluation. The data were collected through a questionnaire, observation,documentation, and interview, and analyzed using the descriptive statistic. The table offrequency distribution and histogram were also presented. The trend for each variablewas computed to know the trend categories based on the categories set.The results of the study show that (1) the educational background of the studentstaking Introduction to Accounting subject consists of vocational school majoring inaccounting (4.44%), senior high school majoring in exact science (80%) and seniorhigh school majoring in social science (15.55%). (2) The students’ motivation iscategorized as medium,(33.33% of the questioner and observation data). (3) Theinfrastructure is quite sufficient,indicated by various media including manuallaboratory and computer laboratory. (4) The use of infrastructure is in afairly goodcategory (44.44%). However, the results of observations show that the use ofinfrastructure for the teaching process is not optimal yet. (5) The teaching process is ina good category (37.77%). (6) The students’ understanding after having the subject is ina good category (51,11%). (7) The students’ score, consisting of mid test, final test andstudent assignments, can be categorized as very good (44.44%).Keywords : Evaluation,Instructional, stake Model